Representation of the “Quality” Category in the Advertising Text of the Turn of the 20th Century (Based on Ural Press) - Rozhkova, Polina A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
This article considers the features of the representation of the category of “quality” in advertising texts at the turn of the twentieth century. The author refers to daily and weekly regional periodicals of the time: Ural’skaia Zhizn’, Ural’skij Listok, Ekaterinburgskaia Nedelia, Delovoi Korrespondent, and Ekaterinburgskaia Gazeta selectively reviewing issues from 1893 to 1917. Although it does not itself produce ideas and meanings as it only applies them for its own needs, advertising as a source is interesting primarily because it reflects the basic values and fashion trends of its era. The aim of the study is to analyze the possible ways of communicating about the quality of the product in a holistic way. In the course of the work, the author identifies 8 tactics for informing the potential buyer about the quality of goods, and several related categories, such as “authenticity”, “authority”, and “status”. The research focuses on the peculiarities of the language design of information about the quality, as well as the analysis of the reasons for the choice by the authors of the advertising of a particular way of presenting this information. Much attention is also paid to the general characteristics of the development of an advertising text at the turn of the twentieth century. An analysis of the tactics of informing the buyer about the quality of the goods also helps draw an approximate “portrait” of the recipient of the advertisement — from rational people, for whom practicality and utility come first, to those who are ready to succumb to manipulation and persuasion choosing a product.